Genital condylomatosis in men and human immunodeficiency virus seropositivity - Tavares, Rogério R.; Passos, Mauro Romero Leal; Cavalcanti, Silvia M.B.; Pinheiro, Vandira M.S.; Rubinstein, Irineu (Brazilian Journal of Sexually Transmitted Diseases, 2000)
This is a transversal, observational study, based on the clinical, laboratorial and epidemiological data collected from the patient recoreis of 1168 male patients who had their first visit 10 the STO Clinic of the Universidade Federal Fluminense (UFF) in Niterói. Brasil. between january. 1996 and december 1997. The objectives of the study were: to determine and to compare the frequencies of genital condylomatous HPV lesions in HIV-negative and in HIV-positive men: to detennine the frequencies of HIV soropositivity and genital condylomatosis of the whole samplc and compare these 10 the literature. A sociocconomical, cultural and sexual behaviour profile of the population studied was also done. Results: Toe frequency of genital condylornmous lesions in HIV-positive men was 12.5% and thal of thc HIV-negative men was 17%. This difference wes not statistically significant (p > 0.05). The HIV soropositivity frequency was 9.9%, compalible with those found in the brazilian medical literature for 1997 for STD clinic patients in othcr cities. Toe frequency of genital condylomatous lesious for the whole sample was 15.8%. comparable to lhe rates for STD male paúcnts found in the international literature.